Crack initiation behavior in single crystalline silicon. (15th March 2017) - Zhao, Lv; Bardel, Didier; Maynadier, Anne; Nelias, Daniel
Abstract: In this article, we report special fracture initiation behavior of (110) cleavage in silicon single crystal. It is found that the static energy release rate always exceeds the material toughness upon crack initiation. According to high-speed imaging measurements and fractographies, it is found that the crack has an important initial velocity, i.e. up to 3000 m/s, and then reaches the steady-state propagation regime very quickly. The experimentally revealed initial crack velocity is in good agreement with estimation from the energy flux at crack initiation. Graphical abstract: